1999
DOI: 10.1177/074391569901800109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Arizona Alcohol Warning Poster

Abstract: An Arizona law, effective January 1, 1992, requires establishments that sell alcohol to display a poster that warns of the risk of drinking alcohol while pregnant. In Study 1, the authors measure the effects of this warning poster on college students before (N = 362), 3 months after (N = 332), 9 months after (N = 369), 12 months after (N = 337), and 18 months after (N = 336) the legislation became effective. After the introduction of the law, students reported more exposure to the poster and greater recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Therefore, images of substance abusers and attributions made to account for their behavior may be viewed as equally important, if not more important, determinants of conformity than perceived health consequences. Consistent with this conclusion, recent work on the effectiveness of warning posters in Arizona shows that the behavioral intentions of pregnant women with regard to alcohol consumption were unaffected despite small learning effects regarding the dangerous consequences of such behavior (MacKinnon et al 1999).…”
supporting
confidence: 55%
“…Therefore, images of substance abusers and attributions made to account for their behavior may be viewed as equally important, if not more important, determinants of conformity than perceived health consequences. Consistent with this conclusion, recent work on the effectiveness of warning posters in Arizona shows that the behavioral intentions of pregnant women with regard to alcohol consumption were unaffected despite small learning effects regarding the dangerous consequences of such behavior (MacKinnon et al 1999).…”
supporting
confidence: 55%
“…Scammon et al (1991) analyzed the impact for before and after new warning label requirement among Mormons and non-Mormons in a comparative way. Similar logistic regression models were constructed by MacKinnon et al (1999) and Fenaughty and MacKinnon (1993) that examined the effects of alcohol warning posters.…”
Section: Customer Based Decisions Modelsmentioning
confidence: 99%
“…Few studies evaluating point-of-sale alcohol warnings have been conducted in the US; those that have been conducted focused on alcohol consumption during pregnancy [10,14,15]. These studies found associations between point-of-sale alcohol warning sign laws and decreased odds of any alcohol use [10], binge drinking [14] among pregnant women, and increased knowledge about the risks of drinking during pregnancy [15], compared to states without such laws. Evidence is mixed for the effectiveness of warning labels on alcohol packaging itself.…”
Section: Introductionmentioning
confidence: 99%